2009
DOI: 10.1590/s0104-42302009000100014
|View full text |Cite
|
Sign up to set email alerts
|

Ultrassonografia e ressonância magnética: estudo comparativo no diagnóstico da esteatose em obesos grau III

Abstract: RESUMO OBJETIVOS.Avaliar a concordância entre a ressonância magnética (RM) e a ultrassonografia abdominal (USG) no diagnóstico da doença hepática gordurosa não-alcoólica (DHGNA), bem como a concordância entre cada método com o exame padrão-ouro histopatológico. MÉTODOS. A população estudada foi constituída por 145 pacientes com obesidade grau III (IMC ≥ 40 Kg/m²), de ambos os sexos. O diagnóstico da DHGNA foi realizado por ultrassonografia e ressonância magnética. Em uma subamostra foi realizado o diagnóstico … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…FL represents a spectrum of liver disorders that are histologically unified by macrovesicular fatty liver in the absence of excessive alcohol intake ( 4 ) ; however, it can cause liver cirrhosis and even liver carcinoma if not treated in time ( 5 , 6 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FL represents a spectrum of liver disorders that are histologically unified by macrovesicular fatty liver in the absence of excessive alcohol intake ( 4 ) ; however, it can cause liver cirrhosis and even liver carcinoma if not treated in time ( 5 , 6 ) .…”
Section: Introductionmentioning
confidence: 99%
“…A EH representa um espectro de distúrbios hepáticos unificados histologicamente pela EH macrovesicular na ausência do consumo excessivo de álcool ( 4 ) , podendo desencadear cirrose hepática e até carcinoma hepático se não for tratada a tempo ( 5 , 6 ) .…”
Section: Introductionunclassified
“…Rodrigues et al 45 analyzed resting metabolic rate by indirect calorimetry in obese patients and found that a tendency towards underestimation of self-reported caloric intake exists among obese women and that the failure to lose weight in some patients can be due to their low level of physical activity. Chaves et al 46 used abdominal ultrasound and magnetic resonance imaging to evaluate non-alcoholic fatty liver disease diagnoses in morbidly obese patients and found significant agreement between the ultrasound method and the hepatic biopsy, which indicates a need to implement and perform more research on the use of ultrasound and to validate these methods. Reliance of such procedures could minimize the need to perform biopsies to detect and diagnose such diseases.…”
Section: Methodsmentioning
confidence: 99%
“…Most individuals with NAFLD characterized by simple steatosis are asymptomatic, thus the disease insidiously develops with few reports of bad feeling and abdominal discomfort. Physical examination may be normal, and at most hepatomegaly is observed ( 6 ) . Routine abdominal ultrasonography (US) reveals much higher prevalence values than those observed in investigations by means of laboratory aminotransferases tests ( 7 ) .…”
Section: Introductionmentioning
confidence: 99%